Structural and Compositional Changes in Erythrocyte Membrane of Obese Compared to Normal-Weight Adolescents - Perona, Javier S.; González-Jiménez, Emilio; Aguilar-Cordero, María J.; Sureda, Antonio; Barceló, Francisca (The Journal of membrane biology, 2013)
Unhealthy dietary habits are key determinants of obesity in adolescents. Assuming that dietary fat profile influences membrane lipid composition, the aim of this study was to analyze structural changes in the erythrocyte membrane of obese compared to normal-weight adolescents. The study was conducted in a group of 11 obese and 11 normal-weight adolescent subjects. The lipid profile, lipid peroxidation and acetylcholinesterase enzyme (AChE) activity were analyzed by conventional methods. The structural properties of reconstituted erythrocyte membrane were characterized by X-ray diffraction. Erythrocyte membrane from obese adolescents had a lipid profile characterized by a higher cholesterol/phospholipid ratio, an increase in saturated fatty acid and a decrease in monounsaturated and n-6 polyunsaturated fatty acid concentrations. Differences in lipid content were associated with changes in the structural properties of reconstituted membranes and the oxidative damage of erythrocyte membrane. The lower oxidative level shown in the obese group (0.15 ± 0.04 vs. 0.20 ± 0.06 nmol/mg for conjugated diene concentrations and 2.43 ± 0.25 vs. 2.83 ± 0.31 nmol/mg protein for malondialdehyde levels) was related to a lower unsaturation index. These changes in membrane structural properties were accompanied by a lower AChE activity (1.64 ± 0.13 vs. 1.91 ± 0.24 nmol AChE/[min mg protein]) in the obese group. The consequences of unhealthy dietary habits in adolescents are reflected in the membrane structural properties and may influence membrane-associated protein activities and functions.